Application of Shuttle Radar Topography Mission Data in Hydrological Analysis of Super Pit and Griffin Coal Mine - Ghosh, Apurna (2016)
In the mining history, inrush of water is always an issue especially for the mines located in heavy rainfall areas. Nowadays, mining companies and research institutes have developed many advanced technologies for study and analysis of hydrological processes. In this paper, an advanced method is introduced, which uses the Shuttle Radar Topography Mission Digital Elevation Model (SRTM DEM) data in Geographical Information System (GIS) platform to simulate the stream distributions around two specific mines viz. Super Pit and Griffin coal mines in Western Australia. The impact of this approach is important, because it reduces the time and economic cost by creating high spatial resolution hydrological map in the specific areas. The results match with the ground reality. Based on the results, the stream structure around Griffin coal mine is more complicated than that of Super Pit. The Bi-furcation ratio and drainage density are computed to estimate the subsoil permeability characteristics of two mines. Recommendations have been put forward to prevent and reduce the potential risks of water accumulation around the open pit mines.